Enhanced N-directed electrophilic C–H borylation generates BN–[5]- and [6]helicenes with improved photophysical properties. Issue 4 (12th January 2022) - Yuan, Kang; Volland, Daniel; Kirschner, Sven; Uzelac, Marina; Nichol, Gary S.; Nowak-Król, Agnieszka; Ingleson, Michael J.
Abstract : An enhanced N-directed electrophilic C–H borylation methodology has been developed that provides access to azaborine containing helicenes. Abstract : Helicenes are chiral polycyclic aromatic hydrocarbons (PAHs) of significant interest, e.g. in supramolecular chemistry, materials science and asymmetric catalysis. Herein an enhanced N-directed electrophilic C–H borylation methodology has been developed that provides access to azaborine containing helicenes (BN–helicenes). This borylation process proceeds via protonation of an aminoborane with bistriflimidic acid. DFT calculations reveal the borenium cation formed by protonation to be more electrophilic than the product derived from aminoborane activation with BBr3 . The synthesised helicenes include BN-analogues of archetypal all carbon [5]- and [6]helicenes. The replacement of a CC with a BN unit (that has a longer bond) on the outer helix increases the strain in the BN congeners and the racemization half-life for a BN–[5]helicene relative to the all carbon [5]helicene. BN incorporation also increases the fluorescence efficiency of the helicenes, a direct effect of BN incorporation altering the distribution of the key frontier orbitals across the helical backbone relative to carbo-helicenes.